Cover Feature: Recent Advances in the Development of Anode Materials for Solid Oxide Fuel Cells Utilizing Liquid Oxygenated Hydrocarbon Fuels: A Mini Review (Energy Technol. 1/2019). Issue 1 (22nd January 2019) - Wang, Wei; Qu, Jifa; Julião, Paulo Sérgio Barros; Shao, Zongping
Abstract : Recent advances in the development of anode materials for solid oxide fuel cells : Solid oxide fuel cells (SOFCs) attracted numerous attentions due to their fuel flexibility, high efficiency and low emissions. Recent advances in the coking‐resistant SOFCs operated on liquid fuels are reviewed with highlights in the design of high‐performance anodes and new liquid oxygenated hydrocarbon fuels. Cover illustrator: Yijun Zhong. More details can be found in the Review by Wei Wang et al. onpage 33 in Issue 1, 2019 (10.1002/ente.201700738 ).